2010
DOI: 10.1177/1367006910363059
|View full text |Cite
|
Sign up to set email alerts
|

Predicting two Mandarin-English bilingual children’s first 50 words: Effects of frequency and relative exposure in the input

Abstract: This study tested two hypotheses that relate children's early words to the input:(1) the language of bilingual children's first words is correlated with their exposure time to each language and (2) children are more likely to acquire words from the first and/or last position in utterances. We tested these hypotheses with spontaneous language use in the families of two Mandarin-English bilingual children, followed longitudinally every three months from 6 months to 18 months. The results showed that the exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Although few studies exist on bilingual children's vocabulary in their ethnic language, common findings indicate that parent language use is very important to development or maintenance of the child's ethnic language (Chan & Nicoladis, 2010;De Houwer, 2007;Lanza, 2001;Pearson, Fernandez, Lewedeg, & Oller, 1997;Wigglesworth & Stavans, 2001). For a child learning two languages with different social status, a lower-status ethnic language is at risk not to be learned or to be later forgotten, especially when the ethnic language receives little attention in school.…”
Section: Parental Language Usementioning
confidence: 99%
“…Although few studies exist on bilingual children's vocabulary in their ethnic language, common findings indicate that parent language use is very important to development or maintenance of the child's ethnic language (Chan & Nicoladis, 2010;De Houwer, 2007;Lanza, 2001;Pearson, Fernandez, Lewedeg, & Oller, 1997;Wigglesworth & Stavans, 2001). For a child learning two languages with different social status, a lower-status ethnic language is at risk not to be learned or to be later forgotten, especially when the ethnic language receives little attention in school.…”
Section: Parental Language Usementioning
confidence: 99%
“…Future studies in which changes in motion properties could be detected as readily as changes in object (e.g., manner) could shed further light concerning infants’ default assumption in word‐mapping. Notwithstanding the need to replicate and expend these findings, this study provides additional evidence that the dominance of a given word class in young word learners found in spontaneous speech data might have been confounded by differences in cultural practices, or methodological limitations of parental‐report measures, such as variations in number of items per word category in vocabulary checklists (Chan & Nicoladis, 2010; Salerni, Assanelli, D’Odorico, & Rossi, 2007; Tardif et al., 1999). We believe that controlled experimental procedures similar to the habituation paradigm used in this study might provide the “purest” measures of infants’ default assumption about word referents.…”
Section: Discussionmentioning
confidence: 80%
“…These data align with a large body of studies that has shown the acquisition of nouns to precede the acquisition of other lexical categories across many languages, with some studies using bilingual participants (cf. Chan & Nicoladis, 2010 , for references to numerous relevant studies).…”
Section: Resultsmentioning
confidence: 99%